2014
DOI: 10.7860/jcdr/2014/8420.4474
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Chemical Surface Treatments of Denture Teeth on Shear Bond Strength: A Comparative Study

Abstract: Background: The development of better cross linked acrylic resin teeth has solved the problems related to wearing and discoloration of acrylic teeth. The same cross linking at ridge lap region acts as a double edge sword as it weakens the bond between denture base and tooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…12 In this study, it was found that, with higher shear bond strength values, higher percentages of cohesive and mixed failures were also evident, which is in accordance with a study by Akin et al 13 CAD/CAM (milled) and heat-polymerized denture bases had similar percentages of cohesive and mixed failures, while coldpolymerized acrylics showed mostly adhesive failures (Table 2). Similar results to our study were obtained by Jain et al 5 and Neppelenbroek et al, 6 who stated that the cohesive failure mode between heat-polymerized denture base resin and acrylic teeth occurred in 100% of instances. The prevalence of cohesive failures suggests that the bond strength between denture base acrylics and prefabricated teeth was higher compared with the resistance of each material alone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…12 In this study, it was found that, with higher shear bond strength values, higher percentages of cohesive and mixed failures were also evident, which is in accordance with a study by Akin et al 13 CAD/CAM (milled) and heat-polymerized denture bases had similar percentages of cohesive and mixed failures, while coldpolymerized acrylics showed mostly adhesive failures (Table 2). Similar results to our study were obtained by Jain et al 5 and Neppelenbroek et al, 6 who stated that the cohesive failure mode between heat-polymerized denture base resin and acrylic teeth occurred in 100% of instances. The prevalence of cohesive failures suggests that the bond strength between denture base acrylics and prefabricated teeth was higher compared with the resistance of each material alone.…”
Section: Discussionsupporting
confidence: 92%
“…[2][3][4] The problem is even greater with implantsupported overdentures because their higher chewing capacity increases the risk of tooth detachment from the overdenture base. 5 Denture base resin and prefabricated teeth differ in a structure and are fabricated separately. Separated fabrication processes are considered to be one of the main factors that can lead to tooth failure, especially in the anterior portion of a removable denture.…”
Section: Introductionmentioning
confidence: 99%
“…13 The group in which monomer application was done prior to packing (i.e., group B) showed higher bond strength value as compared with the control group. The increase in bond strength on monomer application was also reported by Rubina et al, 2 Jain et al, 1 Madhav et al, 14 Patil et al, 15 and Saavedra et al 16 Group C in which removal of the surface glaze was done prior to monomer application showed bond strength better than the control group and monomer application. Grinding the ridge lap surface with an aluminum oxide abrasive stone was seen to significantly increase the bond strength between acrylic teeth and denture base resin, as reported by Bragaglia et al 17 Group D showed the second highest bond strength, that is, dichloromethane solvent application before packing.…”
Section: Discussionsupporting
confidence: 68%
“…Nowadays non-polymerized chemicals such as dichloromethane, chloroform, and some adhesive bonding agents are used to increase bond strength between acrylic teeth and denture base materials. 1 Teeth are the best measure of individuality of a person. Acrylic teeth attached with denture base should demonstrate optimum physical and mechanical properties to withstand rigorous demands of masticatory functions such as chewing, biting, shearing of food, and simultaneously superior esthetics, particularly in the anterior region of the mouth.…”
Section: Introductionmentioning
confidence: 99%
“…Krishna et al[ 10 ] reported that chemical surface treatment of denture teeth with ethyl acetate provided highest bond strength followed by control, chloroform, acetone groups. Jain et al[ 11 ] reported increased bond strength between the denture teeth and heat cure material with use of dichloromethane Consani et al[ 12 ] stated that different polymerization cycle have similar effects on the hardness of heat-activated denture base resin. Grando et al[ 13 ] proved that (Trilos and Saluut) different brands of teeth do not have a difference in their wear resistance.…”
Section: Discussionmentioning
confidence: 99%